2018
DOI: 10.21849/cacd.2018.00262
|View full text |Cite
|
Sign up to set email alerts
|

Joint Video Self-Modeling as a Conversational Intervention for an Individual with Traumatic Brain Injury and His Everyday Partner: A Pilot Investigation

Abstract: Impairments in social discourse and self-awareness often compromise exchanges between individuals with traumatic brain injuries (TBI) and their everyday partners [1,2]. Individuals with TBI present with poor presupposition, unclear referents, problems initiating and maintaining topics, topic repetitiveness, interruptions, tangential topic shifts, verbosity or terseness, vague or overly specific explanations, perseverations, and other inappropriate social behaviors [3][4][5][6][7][8][9]. Those pragmatic impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 68 publications
0
20
0
1
Order By: Relevance
“…Of these, one study had 200 participants, 32 two studies had 20-29 participants 33,34 and four studies had five or fewer participants. 30,[37][38][39] The remaining study did not include any people with TBI. 31 There was considerable heterogeneity in sample characteristics.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, one study had 200 participants, 32 two studies had 20-29 participants 33,34 and four studies had five or fewer participants. 30,[37][38][39] The remaining study did not include any people with TBI. 31 There was considerable heterogeneity in sample characteristics.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Across the eight studies, one study had 200 participants, 32 four studies had 10-64 participants 30,31,33,34 and three studies had fewer than five participants. [37][38][39] Of these, 226 were familiar communication partners (208 spouses/partners of people with TBI, 14 parents, 2 friends and 2 siblings) and 102 were unfamiliar (64 shop assistants,…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…A study using the same training programme with support staff found that trained carers were able to facilitate more positive conversations with people with TBI than untrained carers (Behn, Togher, Power, & Heard, 2012). A single case study involving one person with TBI and his spouse using video selfmodelling to target communication partner behaviours (decreased use of testing questions and increased use of memory supports) also showed improvements in the quality of conversations (Hoepner & Olson, 2018).…”
Section: Introductionmentioning
confidence: 98%